Pengaruh Antiscatter grid Terhadap Dosis dan Kualitas Citra pada Prosedur Radiologi Intervensional - Eka Aulia Ardyanti; M. Roslan Abdul Gani; Lukmanda Evan Lubis; Djarwani Soeharso Soejoko (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2019)
The study discusses the threshold of thickness required for antiscatter grid use on Siemens Artis Zee at “Dharmais” National Cancer Center, Jakarta. The device has adjustable modes of low, medium, and high fluoroscopy. Patients are represented by Polymethyl Methacrylate (PMMA) phantom with a thickness variation of 7-22 cm of 1 cm interval. The dose metrics was measured as the entrance skin dose (ESD) and the transmission dose, while the image quality metric employed being signal to noise ratio (SNR), leading the result to FOM as squared SNR per dose. The FOM bridged dose and image quality to determine threshold of antiscatter grid usage on fluoroscopy based on fantom thickness. As a result, antiscatter grid are recommended to be used for objects 11 cm and thicker on the use of low fluoroscopy mode, and 16 cm and thicker objects on high fluoroscopy mode. In medium fluoroscopy mode, no threshold was yielded due to tube current being higher than other modes, hence it is recommended to remove the antiscatter grid during the use of the medium fluoroscopy mode